A draft nuclear-genome assembly of the acoel flatworm Praesagittifera naikaiensis. Issue 4 (6th April 2019) - Arimoto, Asuka; Hikosaka-Katayama, Tomoe; Hikosaka, Akira; Tagawa, Kuni; Inoue, Toyoshige; Ueki, Tatsuya; Yoshida, Masa-aki; Kanda, Miyuki; Shoguchi, Eiichi; Hisata, Kanako; Satoh, Noriyuki
Abstract: Background: Acoels are primitive bilaterians with very simple soft bodies, in which many organs, including the gut, are not developed. They provide platforms for studying molecular and developmental mechanisms involved in the formation of the basic bilaterian body plan, whole-body regeneration, and symbiosis with photosynthetic microalgae. Because genomic information is essential for future research on acoel biology, we sequenced and assembled the nuclear genome of an acoel, Praesagittifera naikaiensis . Findings: To avoid sequence contamination derived from symbiotic microalgae, DNA was extracted from embryos that were free of algae. More than 290x sequencing coverage was achieved using a combination of Illumina (paired-end and mate-pair libraries) and PacBio sequencing. RNA sequencing and Iso-Seq data from embryos, larvae, and adults were also obtained. First, a preliminary ∼17–kilobase pair (kb) mitochondrial genome was assembled, which was deleted from the nuclear sequence assembly. As a result, a draft nuclear genome assembly was ∼656 Mb in length, with a scaffold N50 of 117 kb and a contig N50 of 57 kb. Although ∼70% of the assembled sequences were likely composed of repetitive sequences that include DNA transposons and retrotransposons, the draft genome was estimated to contain 22, 143 protein-coding genes, ∼99% of which were substantiated by corresponding transcripts. We could not find horizontally transferred microalgal genes in the acoel genome. Benchmarking Universal Single-Copy Orthologs analyses indicated that 77% of the conserved single-copy genes were complete. Pfam domain analyses provided a basic set of gene families for transcription factors and signaling molecules. Conclusions: Our present sequencing and assembly of the P. naikaiensis nuclear genome are comparable to those of other metazoan genomes, providing basic information for future studies of genic and genomic attributes of this animal group. Such studies may shed light on the origins and evolution of simple bilaterians.